Students’ Anxieties in EFL Speaking Class - Ridho Hafizh Firdaus; Wawan Wahyudin; Tatu Siti Rohbiah (Journal of English Language Teaching and Cultural Studies, 2022)
This study is focused on identifying the factor of students’ anxiety and solution to reduce anxiety in speaking English at the third Semester Students of English Education Department of Universitas Islam Negeri Sultan Maulana Hasanuddin Banten in Academic Year 2021/2022. The formulated problems of this study were: (1) What are the causes of students’ anxiety in speaking English? (2) How are the solutions to reduce students’ anxiety in speaking English? The method used qualitative method. The participants of this study were third semester students majoring in English Education at Universitas Islam Negeri Sultan Maulana Hasanuddin Banten. The data were gathered through questionnaire and interview.  The results of this study: first, personal and interpersonal students’ fear in speaking English cause low self-confidence. Second, the students’ perceptions, they fell apprehensive about speaking in front of the class. Third, lecturer-students interaction, the students sensed anxiety when they don't understand what the lecturer is correcting. The last is the lack of preparation, according to the students; they are concerned about their lack of preparation for tests or speaking in front of the class. The solution to reduce anxiety; the students said trying to be confident, preparing material, and they don't be scared to make mistakes when speaking because correcting the errors will help them speak more confident.